Suitability Analysis of Readymade Bituminous Pothole Patching Mix in Nepal - Kayastha, Sahanshila (Madhesh Journal of Interdisciplinary Research, 2026)
The objective of the study is the analysis of the suitability of Readymade Bituminous Pothole Patching Mix for pothole repair in the case of Road Division Bharatpur, Nepal. It is performed since 2019 in the national highways lies in Chitwan district and Dhading district of Nepal which is under supervision of Road Division Bharatpur, Nepal. The lab tests of aggregate have been performed in the lab of Road division Bharatpur and the test of bitumen were done in the supplier’s laboratory only. The aggregates being used for the production of Readymade bituminous pothole patching mix is satisfying the requirements of IRC: 2014, the rate of Readymade bituminous mix is more economical than the Hot mix method and Cold mix method. A scheduled questionnaire survey has been conducted with engineers and supervisor of the road division Bharatpur. From the questionnaire it was concluded that Low Energy Use for Production and Placement, Paving Operation Benefit, Obtain Desired Density, Low Air Void Contents, Minimize Fume and Odor, Stiffness and Rutting Resistant and Less Fatigue and Thermal Cracking are the main factors obtained from RDB Engineers, supervisors and length workers. This Readymade pothole patching mix can be stockpiled and remains workable for at least 6 months and can be used even in rainy season.